(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: This study examined parent perceptions towards child vaccinations, and sources used leading to inoculation decisions. Methods: A survey was electronically dispersed to parents to examine their perceptions of vaccinations, what source they used to form their decisions, and whether or not they have their children vaccinated. Results: Significant differences on perceptions about vaccinations, those who followed the recommended vaccination schedule, and what sources of information they used were found. There was a significant relationship between parents who ranked using social media as their primary source and reports that they did not, or will not, vaccinate their children. Conclusions: Where parents obtain health-related information was shown to be a significant factor on vaccine perceptions and whether children were inoculated or not.